TEACHING DURING PANDEMIC; IMPACT ON STUDENTS’ ENGLISH SKILLS OF JUNIOR HIGH SCHOOL - Zurniati, Vivi; Astuti, Indri; Efrina, Gusnita (Universitas PGRI Sumatera Barat, 2022)
This paper investigates the impact of online teaching and learning undertaken during pandemic of Covid-19 on students’ English skills. The skills include speaking, listening, reading, and writing skills. This study used a qualitative method with a descriptive approach exploring what skills got impacted of 2 years online learning situation. Students' English skill, in particular, speaking and listening skills were negatively affected by the application of online learning that they had been done in prior. While, reading and writing skills had a positive impact on students' English skills as it used Geschool application therefore reading skills were more taught. This learning also made students do writing activities such as writing material from learning videos. The observation activities showed students were better able to participate in reading and writing lessons. The resdult of this studi was also indicated that in general English skills were badly affected which was showed by the average value of students was 50. Mpreover, all of those skills were impacted due to inadequate of facilities, motivation, and affectiveness of online teaching itself.Makalah ini menyelidiki dampak pengajaran dan pembelajaran online yang berjalan selama pandemi Covid-19 terhadap kemampuan Bahasa Inggris siswa. Keterampilan tersebut meliputi keterampilan berbicara, mendengarkan, membaca, dan menulis. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif yang mengeksplorasi keterampilan apa saja yang dipengaruhi oleh situasi pembelajaran online selama 2 tahun. Keterampilan bahasa Inggris siswa khususnya keterampilan berbicara dan mendengarkan dipengaruhi secara negatif oleh penerapan pembelajaran online yang telah mereka lakukan sebelumnya. Sedangkan keterampilan membaca dan menulis berdampak positif terhadap kemampuan bahasa Inggris siswa karena menggunakan aplikasi Geschool sehingga keterampilan membaca lebih banyak diajarkan. Pembelajaran ini juga membuat siswa melakukan kegiatan menulis seperti menulis materi dari video pembelajaran. Kegiatan observasi menunjukkan siswa lebih mampu berpartisipasi dalam pelajaran membaca dan menulis. Hasil penelitian ini juga menunjukkan bahwa secara umum keterampilan Bahasa Inggris sangat terpengaruh yang ditunjukkan dengan nilai rata-rata siswa adalah 50. Selain itu, semua keterampilan tersebut terpengaruh karena kurangnya fasilitas, motivasi, dan afektif pengajaran online itu sendiri.